Head Trauma from Falling Increases Subsequent Emergency Department Visits More Than Other Fall‐Related Injuries in Older Adults. Issue 4 (April 2016) - Southerland, Lauren T.; Stephens, Julie A.; Robinson, Shari; Falk, James; Phieffer, Laura; Rosenthal, Joseph A.; Caterino, Jeffrey M.
Abstract : Objectives: To determine whether fall‐related injuries affect return to the ED after the initial visit. Design: Retrospective chart review. Setting: Academic Level 1 trauma center ED. Participants: Individuals aged 65 and older evaluated for a fall from standing height or less and discharged (N = 263, average age 77, 70% female). Measurements: After institutional review board approval, electronic medical record data were queried. Univariate and multivariable logistic regression models were used to determine factors associated with risk of returning to the ED within 90 days. Results: Injuries included fractures (45%, n = 117); head trauma (22%, n = 58); abrasions, lacerations, or contusions (34%, n = 88); and none (22%, n = 57). Emergency care was frequently required, with 13 (5%, 95% confidence interval (CI) = 2.3–7.6%) returning within 72 hours, 35 (13%, 95% CI = 9.2–17%] within 30 days, and 57 (22%, 95% CI = 17–27%) within 90 days. Univariately, the odds of returning to the ED within 90 days was more than two times as high for those with head trauma as for those without (odds ratio = 2.66). This remained significant in the multivariable model, which controlled for Charlson Comorbidity Index, fractures, soft tissue injuries, and ED observation unit use. Conclusion: More than one‐third of older adults with minor head trauma from a fall will need to return to the ED in the following 90 days. These individuals should receive close attention from primary care providers. The link between minor head trauma and ED recidivism is a new finding.